Effect of foliar nutrition on growth and yield of cotton (Gossypium herbaceum) MCU 5 - KUMAR, N SENTHIL; RAJASEKAR, M; PARAMSIVAN, M; KUMANAN, K (The Indian Journal of Agricultural Sciences, 2023)
From the experimental results, it is inferred that cotton crop responds well to the foliar nutrition with zinc and magnesium. Application of these nutrients through foliar spray might be the feasible option to control the yield barrier under rainfed condition. Further the study found that foliar spraying of MgSO4 1.0% along with 0.5% of ZnSO4 three times respectively at squaring, flowering and boll formation stages markedly improved the plant growth and seed cotton yield. Thus, these treatments may be recommended for enhancing the rainfed cotton yield but location specificity verification is required before recommendation.